2015
DOI: 10.1007/s10936-015-9374-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing Control Information in a Nominal Control Construction: An Eye-Tracking Study

Abstract: In an eye-tracking experiment, we examined the processing of the nominal control construction. Participants' eye-movements were monitored while they read sentences that included either giver control nominals (e.g. promise in Luke's promise to Sophia to photograph himself) or recipient control nominals (e.g. plea in Luke's plea to Sophia to photograph herself). In order to examine both the initial access of control information, and its later use in on-line processing, we combined a manipulation of nominal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Interference effects are predicted under cue-based retrieval accounts (e.g., Lewis & Vasishth, 2005) and were found for healthy speakers in pronoun resolution (e.g., Badecker & Straub, 2002;Patterson, Trompelt, & Felser, 2014;Schroeder, 2007) and in sentences with control (Kwon & Sturt, 2016). In IWA, interference has been studied under the intervener hypothesis according to which IWA have difficulties when an element similar to the target of the dependency structurally intervenes in a dependency chain (e.g, Engel, Shapiro, & Love, 2018).…”
Section: Canonicity Effects In Sentence Comprehension Canonicity Effmentioning
confidence: 99%
“…Interference effects are predicted under cue-based retrieval accounts (e.g., Lewis & Vasishth, 2005) and were found for healthy speakers in pronoun resolution (e.g., Badecker & Straub, 2002;Patterson, Trompelt, & Felser, 2014;Schroeder, 2007) and in sentences with control (Kwon & Sturt, 2016). In IWA, interference has been studied under the intervener hypothesis according to which IWA have difficulties when an element similar to the target of the dependency structurally intervenes in a dependency chain (e.g, Engel, Shapiro, & Love, 2018).…”
Section: Canonicity Effects In Sentence Comprehension Canonicity Effmentioning
confidence: 99%
“…Why might the reflexive antecedent retrieval system fail to experience interference from grammatically inaccessible antecedents in WhFGD contexts, while showing evidence of such interference in reflexive antecedent retrieval mediated by the related long-distance dependencies of raising and control studied in Kwon and Sturt ( 2015 ) and Sturt and Kwon ( 2015 )? We speculate that the active nature of the WhFGD formation process may provide an explanation for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on reflexive antecedent retrieval in configurations similar to WhFGDs in that they involve an NP associated with a subsequent, unpronounced position similar to a gap has found mixed results. Kwon and Sturt ( 2015 ) investigated reflexive antecedent retrieval in the context of nominal control constructions like (14). Control constructions of this kind resemble WhFGDs in that they can involve a dependency between a displaced NP [ Luke in (14-b)] and a position in an embedded clause [the subject position of to photograph himself in (14-b)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the incongruous conditions will show longer reading times at the embedded verb marked with – si – when compared with their congruous counterpart sentences with the H subject (H-H and H-NH conditions). Crucially, although control information is accessed early during on-line sentence processing (Kwon and Sturt, 2014, 2016a), it has been also shown that the processing of subject-verb honorific agreement can be affected by a feature-matching yet structurally illicit distractor in a control construction (Sturt and Kwon, 2015). If so, we predict that the reading time penalty for the incongruous condition will be reduced in the NH-H condition, where the distractor matches the honorific features of the verb, compared to the NH-NH condition, where it does not, resulting in an interaction between the honorific features of the subject and the dative object at the embedded verb position.…”
Section: Methodsmentioning
confidence: 99%